Users’ Views Regarding Electronic Prescribing Implementation: A Qualitative Case Study in A Private Hospital of Magelang City, Indonesia - Eulalia Puji Febri Kurniawati; Aris Widayati (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2022)
The use of the Internet and digital system in a hospital named the Hospital Information System (HIS) has grown rapidly and remarkably, including in Indonesia. One of the HIS components is electronic prescribing (e-prescribing). Although the Indonesian government has mandated HIS in hospitals since 2011, successful implementation is not without challenges. Therefore, this study aimed to explore users' views regarding e-prescribing implementation through a case study in a private hospital in Magelang City, Indonesia. This study applied a qualitative approach. Participants were e-prescribing users who were selected purposively. Data were gathered using interviews. The Capability, Opportunity, Motivation, and Behavior (COM-B) model was used to structure the interview guideline. Data were transcribed verbatim and analyzed using a thematic approach. Twenty participants were interviewed. Five themes emerged through the interviews: self-reflection, perceived advantages, policy, capacity building, and quality assurance. The themes express optimism in implementing e-prescribing. Users are central to e-prescribing system acceptance, as is explained in the self-reflection and perceived advantages themes. Furthermore, top management plays a pivotal role in improving the capacity and ensuring system implementation quality. This study’s findings imply that the user, system, and organization play crucial roles in enhancing health care service quality through e-prescribing.